EFEKTIFITAS HEALTH EDUCATION TENTANG KEBERSIHAN GENETALIA TERHADAP PENGETAHUAN PENCEGAHAN FLOUR ALBUS PADA REMAJA PUTRI DI MTS AL AL-MASâUDY MOJOKERTO - Khalimatus SaÃ¢Â€Â™diya, Lida (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Reproductive health education in schools is done through curricular programs are incorporated into and extracurricular subjects such as education (health education). Generally reproductive health education in schools which do cederung successful because the school is able to reach the population more directly than other health care institutions. The purpose of this study was to analyze the effectiveness of health education about genital hygiene for prevention of flour albus knowledge in adolescent girls. This study design is pre experiment with approaches One-Group Pre-Post Test Design. The population was around all the girls were 83 respondents and samples were taken with total sampling technique sampling. Data taken using a questionnaire instrument on prevention knowledge whitish, then analyzed editing, coding, scoring and tabulating and tested with cross tabs. The results showed no effectiveness of health education on hygiene genitalia towards knowledge flour albus on teenage girls in class IX MTs AL-MASUDY Village Simbaringin Kutorejo District of Mojokerto as evidenced by the results of cross tabulation (cross-tabs) data obtained after the change of given health education an increase in the percentage of respondents who pengetahunya enough by 56.6%. Health education is a primary capital to be done in the community in order to prevent discharge. So expect the higher level of public knowledge will further increase the level of health in this study, especially on taking care of the genitalia of knowledge whitish Keywords: Health Education, Knowledge and Flour Albus